Simultaneous recording of laser-evoked brain potentials and continuous, high-field functional magnetic resonance imaging in humans. - Iannetti, G; Niazy, R; Wise, R; Jezzard, P; Brooks, J; Zambreanu, L; Vennart, W; Matthews, P; Tracey, I (2005)
Simultaneous recording of event-related electroencephalographic (EEG) and functional magnetic resonance imaging (fMRI) responses has the potential to provide information on how the human brain reacts to an external stimulus with unique spatial and temporal resolution. However, in most studies combining the two techniques, the acquisition of functional MR images has been interleaved with the recording of evoked potentials. In this study we investigated the feasibility of recording pain-related evoked potentials during continuous and simultaneous collection of blood oxygen level-dependent (BOLD) functional MR images at 3 T. Brain potentials were elicited by selective stimulation of cutaneous Adelta and C nociceptors using brief radiant laser pulses (laser-evoked potentials, LEPs). MR-induced artifacts on EEG data were removed using a novel algorithm. Latencies, amplitudes, and scalp distribution of LEPs recorded during fMRI were not significantly different from those recorded in a control session outside of the MR scanner using the same equipment and experimental design. Stability tests confirmed that MR-image quality was not impaired by the evoked potential recording, beyond signal loss related to magnetic susceptibility differences local to the electrodes. fMRI results were consistent with our previous studies of brain activity in response to nociceptive stimulation. These results demonstrate the feasibility of recording reliable pain-related LEPs and fMRI responses simultaneously. Because LEPs collected during fMRI and those collected in a control session show remarkable similarity, for many experimental designs the integration of LEP and fMRI data collected in separate, single-modality acquisitions may be appropriate. Truly simultaneous recording of LEPs and fMRI is still desirable in specific experimental conditions, such as single-trial, learning, and pharmacological studies.